HUBUNGAN PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF DENGAN MOTIVASI BELAJAR SISWA KELAS IV SD NEGERI 164 PEKANBARU PADA PEMBELAJARAN IPA - Destri Mustika; Zariul Antosa; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: this research was effected by the observations at the time of the teacher in the process of teaching and learning in the classroom. Some much less motivated students will be learning provided by the teacher, since there is no variation in media support to help learning activities. The purpose of this research was to see the connections between media interactive learning with the learning motivation of students of class IV In SD Negeri 164 Pekanbaru On Learning the the science of nature. This research was carried out in class IV SD Negeri 164 Pekanbaru consisting of class IVa, IVb, and IVc. The sample in this study is the whole grade IV in SD164 Pekanbaru with a total of State In SD Negeri 164 Pekanbaru 127 students. Sampling techniques are used namely total sampling. The results of the research there is a significant relationship between media use interactive learning with the learning motivation of students of class IV SD Negeri 164 Pekanbaru On Learning the the science of nature, with the results of the calculations is: class IV A rcount of incoming 0.505 within 0.40 – 0.599 with a degree of relationship